Presidential Power and the Judicialization of Politics as Determinants of Institutional Change in the Judiciary: The Supreme Court of Ecuador (1979-2009) - Basabe-Serrano, Santiago (2014)
What explains institutional instability in national judicial institutions? Much extant research focuses on de facto institutional instability, emphasizing political motivations behind irregular changes to high court composition. In contrast, I consider the causes for de jure chan- ges made to the Ecuadorian Supreme Court from 1979 to the present, drawing on qualitative and quantitative analyses. I contend that the judicialization of politics and presidential interest in stacking the courts are central explanatory factors, and that changes to the Supreme Court's institutional framework reflect implicit compromises and political arrangements negotiated by strategic political actors. As such, institutional reforms to national judicial instiuttions may beadopted to ameliorate conflict in the larger political sphere.